Conflict Between India and China and Its Impact on Afghanistan (Journal of Social Sciences Review, 2024)
This India-China conflict directly affects Afghanistan's territory politically and economically, especially in terms of security, especially when it comes to territorial disputes and geopolitical competition. This paper pays attention to the dynamics of the India-China rivalry and the controversial impact of this rivalry with Afghanistan, which is of strategic importance in South Asia. The study, through Realism and Dependency Theory application, presents the origins and reasons for actions taken by India and China in Afghanistan, arguing on the fact that these two countries invest in diverse development, governance, and regional security in their diverse motivations and strategies toward Afghanistan. India uses soft power through its infrastructure development, humanitarian aid, and democratic institution building as a counterweight to Pakistan's influence while encouraging longer-term partnership development. China, on the other hand, is pursuing a pragmatic economic engagement approach through the Belt and Road Initiative and also links the security concerns relevant to its Xinjiang region. Thus, Afghanistan is located right at the convergence of these interests but would figure out how to balance conflicting relationships while handling internal instability. The analysis really describes many impacts: fragmented development approaches, the emergence of political differences, and overlapping security strategies, among others. The conclusion drawn from the discussion in this article is that Afghanistan will be able to determine its stability and prosperity by how the country chooses to navigate these dynamics. The paper's argument is for collective regional frameworks as the way to take the adverse effects of such conflicts and advance a balanced approach to initiatives and security.
Keywords: India; China; Afghanistan; Conflict; Territorial Disputes; Xingjiang Region; Political Difference